Introduction to Bibliometric Studies for Lecturers of the Faculty of Health Sciences, Universitas Muhammadiyah Palangkaraya - Mohammad Rizki Fadhil Pratama; Muhamad Riza Syah Fahlevi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Bibliometric studies have become a new standard in finding gap research for further research. Mastering software such as VOSViewer can be beneficial in carrying out these bibliometric studies utilizing databases of international scientific publications. However, bibliometric research still needs to be discovered by some academics, especially those unfamiliar with it, such as lecturers at the Faculty of Health Sciences, Universitas Muhammadiyah Palangkaraya. Therefore, this service activity aims to introduce and train these lecturers regarding bibliometric studies using VOSviewer. The solution offered by the servant is to carry out introductory activities and training in operating VOSviewer in carrying out the bibliometric study. Apart from introducing the lecturers to the branch of science, which is currently in great demand worldwide, it also increases the enthusiasm for writing for the participants. Through the activities, the participants have carried out a bibliometric study in Pharmacy and Medical Laboratory Technology, which can then be published as a separate bibliometric study. As a follow-up to this activity, apart from being able to do it for lecturers in other faculties within the Universitas Muhammadiyah Palangkaraya, training is also planned to be carried out to publish scientific articles on the results of the bibliometric study.